PENGARUH JENJANG PENDIDIKAN DAN SKALA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM KECAMATAN PAMULANG KOTA TANGERANG SELATAN - eka kusuma dewi; Purwatiningsih Purwatiningsih (LPPM Universitas Putera Batam, 2021)
One of the big problems of SMEs that happen in Indonesia is manual bookkeeping. Therefore, it leads to difficulty in calculating turnover, gross profit, and net profit, inhibiting SMEs from growing and scaling up the business. This study aims to observe and determine whether there is an influence of Education Level and Business Scale on the Use of Accounting Information in SMEs in Pamulang District Tangerang Selatan. The tests carried out show that the education level variable significantly affects and the business scale variable does not influence users of accounting information. Based on the F test, it is known that the level of education and the scale of business together significantly affect users of accounting information. So it can be concluded that the results of this study indicate that the education level of the MSME actors affects the use of accounting information in their respective units